2021
DOI: 10.3389/fpsyg.2021.731306
|View full text |Cite
|
Sign up to set email alerts
|

The Rate and Risk Factors of Postpartum Depression in Vietnam From 2010 to 2020: A Literature Review

Abstract: Background: Postpartum depression (PPD) is commonly seen in women after birth and can lead to adverse effects on both the health of mothers and child(ren) development. In Vietnam, there have been a number of studies examining the rate and risk factors of PPD, but none has provided a systematic review.Aim: This current literature review aims to summarize and synthesize the current state of knowledge of studies conducted in Vietnam to provide a comprehensive understanding of the PPD phenomena during the last 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Lack of family support and lower relationship satisfaction were identified as risk factors of PPD [ 25 , 26 ]. It was reported in Indian and Thai studies that marital conflict is independently associated with perinatal depression in women [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lack of family support and lower relationship satisfaction were identified as risk factors of PPD [ 25 , 26 ]. It was reported in Indian and Thai studies that marital conflict is independently associated with perinatal depression in women [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Vietnam, despite the high prevalence of mental illnesses (14.9%), mental health care is only offered for severe illnesses such as schizophrenia and epilepsy and is offered only at tertiary hospitals ( Vuong et al ., 2011 ). Other prevalent conditions such as postpartum depression (PPD) are not recorded as mental health illnesses in the statistic health yearbook despite their high prevalence (ranging from 8.2% to 37.1%) ( Nguyen et al ., 2021 ). One possible explanation could be the sociocultural belief around it being a normal condition due to hormonal changes after delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Other systematic reviews go along the same lines, and in the same journal and section Frontiers in Psychology . For example, Dickson and Schubert ( 2020 ) and Liu et al ( 2022 ) found only six studies in a review of great interest; the study by Nguyen et al ( 2021 ) identified 18 eligible articles; Shou et al ( 2022 ) with 12 studies included; or Tarchi et al ( 2021 ); Huang ( 2022 ) found seven studies for quantitative analysis and eight for indirect evidence; Coxen et al ( 2021 ) with 21 articles included in the focal analyzes of the systematic review. The number of studies to be representative is not defined by the number but by the existence of such studies.…”
Section: Discussionmentioning
confidence: 99%